IDENTIFICATION OF QUANTITATIVE AND QUALITATIVE TRAITS DIVERSITY IN LOCAL BUFFALO IN NAGAN RAYA DISTRICT - Abdullah, Mohd Agus Nashri; Mutawalli, Mutawalli; Ammar, Muhammad; Sari, Eka Meutia (Jurnal Kedokteran Hewan, 2024)
b-districts, Beutong and Seunagan, with 45 buffalo samples from each sub-district. The survey method with random buffalo sampling was employed in this study. The selection of the two research sub-districts was based on the highest buffalo population numbers in Nagan Raya District. The research locations were chosen from six villages: Babah Krueng, Gunong Nagan, Blang Seunong, Sapek, Alue Dodok, and Blang Pateuk. Primary data were obtained from measuring several quantitative traits of buffaloes aged 2.5-3.0 years in the field. All data were analyzed using descriptive statistics. The research results show that the quantitative traits based on the coefficient of variation (CV) of body measurements of buffaloes in Nagan Raya vary considerably. The body measurements of male buffaloes in Beutong Sub-District showed chest circumference, shoulder height, and body length of 172.70 cm, 121.84 cm, and 111.48 cm, respectively, while the female buffalo's chest circumference, shoulder height, and body length were 180.86 cm, 122.18 cm, and 119.32 cm, respectively. The body measurements of male buffaloes in Seunagan Sub-District showed chest circumference, shoulder height, and body length of 169.23 cm, 115.91 cm, and 105.23 cm, respectively, while the female buffalo's chest circumference, shoulder height, and body length were 187.89 cm, 123.04 cm, and 117.39 cm, respectively. The qualitative and quantitative traits of buffaloes measured in these two subdistricts show differences due to different environmental vegetation.